2017
DOI: 10.1007/s12687-017-0313-9
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging community-based participatory research capacity to recruit Pacific Islanders into a genetics study

Abstract: Pacific Islanders face many health disparities, including higher rates of cardiovascular disease, cancer, obesity, and diabetes compared to other racial and ethnic groups. Specifically, the Marshallese population suffers disproportionately from type 2 diabetes, with rates 400% higher than the general US population. As part of an ongoing community-based participatory research (CBPR) partnership, 148 participants were recruited for a study examining genetic variants to better understand diabetes. Participants pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 55 publications
3
34
0
Order By: Relevance
“…9,[27][28][29][30][31][32][33][34][35][36] However, the findings are consistent with a small number of more recent studies that document a willingness to participate among racial and ethnic minorities. [37][38][39] This study adds to the growing body of literature suggesting barriers beyond willingness. [37][38][39] Specifically, the paradoxical findings of this study, which showed no difference in the participation rates of racial/ethnic minorities, yet also showed racial/ethnic minorities report both more opportunity and more willingness, needs further exploration.…”
Section: Wwwcts-journalcommentioning
confidence: 88%
See 1 more Smart Citation
“…9,[27][28][29][30][31][32][33][34][35][36] However, the findings are consistent with a small number of more recent studies that document a willingness to participate among racial and ethnic minorities. [37][38][39] This study adds to the growing body of literature suggesting barriers beyond willingness. [37][38][39] Specifically, the paradoxical findings of this study, which showed no difference in the participation rates of racial/ethnic minorities, yet also showed racial/ethnic minorities report both more opportunity and more willingness, needs further exploration.…”
Section: Wwwcts-journalcommentioning
confidence: 88%
“…[37][38][39] This study adds to the growing body of literature suggesting barriers beyond willingness. [37][38][39] Specifically, the paradoxical findings of this study, which showed no difference in the participation rates of racial/ethnic minorities, yet also showed racial/ethnic minorities report both more opportunity and more willingness, needs further exploration.…”
Section: Wwwcts-journalcommentioning
confidence: 88%
“…When it was not possible to raise a consensus, the situation was outlined, and the main opinions and reasons for disagreement were analysed and subjected to posterior reflection. Importantly, this has not just been a one-off, or sporadic, exercise and similar examples of deliberative community engagement can increasingly be noted in a global context, for instance, in the cases of the University of California biorepositories, the Mayo Clinic Biobank and community-based participatory research partnerships such as recently reported research involving Pacific Islanders as research collaborators (Dry et al 2017 ; Olson et al 2013 ; McElfish et al 2017 ).…”
Section: Contemporary Health Research: Key Features Of a Participatormentioning
confidence: 99%
“…For individuals with a suspected genetic condition, participation in EGS research may be seen as a "last frontier" that enables families to feel that everything possible to find a diagnosis has been done (Halverson, Clift, & McCormick, 2016). This characteristic of EGS may be perceived as a relative ad- ing Pacific Islanders living in Arkansas utilized CBPR approaches to identify diabetes as a common and substantial problem among the population, and achieved a 95% recruitment rate for a study focused on its genetic etiology (McElfish et al, 2017). Participants in that project emphasized that they were more willing to participate, even in intensive projects, if the topic was relevant to them.…”
Section: Broadening Egs Research Engagement: Knowledge and Persuasionmentioning
confidence: 99%